Der industrialisierte Tod - Warburg, Jens (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
The articles explores how the way in which wars are being waged has changed since the 19th century. lts main focus is on ground warfare. Warfare, according to the thesis advocated in the article, has become industrialized within a few decades. One of the consequences was that since then only rarely battles have been lead face to face. Another result was a change in the way the military had to prepare for war. After presenting a short overview the articles proceeds to deal with objectification tendencies in regard to death, which also began to develop in pre-industrial periods.